Antioxidant Activity, Antibacterial Activity, Water Content, and Ash Content In Baduy Honey - Adri Nora; Anjas Wilapangga; Titta Novianti (UNIVERSITAS NEGERI PADANG, 2018)
Indonesia as a tropical country has many different types of honey. Honey was known to have many advantages especially in health promotion as antioxidant and antibacterial. Baduy honey is one of Indonesian forest honey which its nutritional value, antioxidant, and antibacterial activity have not been investigated yet. The purpose of this study to determine antioxidant activity, antibacterial, water content, and also ash content of baduy honey. The research method are DPPH radical scavenging-activity for antioxidant, microplate resazurine assay for antibacterial, qualitative photochemistry analysis, and gravimetric analysis for measuring water and ash content. The result showed that black and yellow baduy honey has water content 18,64% dan 19,32% respectively and ash content 0,32% dan 0,04% respectively. Baduy honey has also containing flavonoid, terpenoid, and alkaloid compounds. Black Baduy honey has higher antioxidant activity than Yellow Baduy honey in which EC 50 values are 1000,79 μg/mL and 1475,28 μg/mL respectively. However, Baduy honey did not show any antibacterial activity againts Escheria coli dan Staphlococcus aureus because of MIC value for both type of honey are tremendously large with 500000 μg/mL.